Rizal without the overcoat - Ocampo, Ambeth R. (Pasig City Anvil, 2008)
"An updated and expanded edition of the best-selling title that offers fresh insights on the life and times of our National Hero. Here, Ocampo has succeeded where other historians have failed-- and that is in making the study and reading of Rizal not a burden, but a joy."--Publisher's description.
Prologue -- Facts and possibilities -- Family and others -- Everyday Rizal -- Legendary talent -- The never-ending story -- Epilogue (the last word) -- Postscripts - Our Rizal's (the 1996 Inquirer Rizal Series) -- Sources.
Keywords: Rizal, Jose -- 1861-1896.; Nationalists -- Philippines -- Biography; Philippines -- History -- Revolution, 1896-1898.